DETERMINAÇÃO DA BIOMASSA DE DIFERENTES ESPÉCIES DE PINUS DA REGIÃO DE AQUIDAUANA, MATO GROSSO DO SUL - SIMPLICIO, Vitor Hugo dos Santos; URBANO, Edilson; SIMPLICIO, Viviane dos Santos (ANAIS DO ENIC, 2022)
-